Tauzī‘ wa Tanwī‘ Bunūd As'islah Ikhtibār An-Nahw li-shaff Ats-Tsālis Al-mutawašithah: Distribution and Diversification of Arabic Grammar Test Items for The Third Grade of Junior High School - Ibnu Hafid Alfarisy; Moh. Ainin; Moh. Khasairi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
In preparing the test items, the test maker must take care of using suitable type of test items and diversifying it. Each test item has criteria, advantages, and disadvantages that need to be considered. This research aims to reveal the distribution and diversification of Arabic grammar test items for the third grade in the Junior High School in Batu City. The research is qualitative and descriptive, as it describes the research sample according to a theory and reveals the hidden phenomena. The primary research sample is the Arabic grammar test items for the third grade of Junior High School in the 2019-2020 school year that include the contents taken from the textbook "An-nahwu Al-wadih". The research concluded that the teacher diversified the test with some types of tests. The test is divided into four types of test that include objective and subjective tests such as multiple choice, short answer, completion or filling the blank, and essay. The comprehensive preparation prepared by the evaluation administrations, such as the test item outline, will help the question maker develop the skills of preparing test items. Keywords: Arabic Grammar, Diversification, Evaluation, Items Test, Nahwu, Syntax.   ملخص عند إعداد بنود الاختبار ، يجب على معد الاختبار أن يعتني باستخدام النوع المناسب من بنود الاختبار وتنويعه. لكل بوع الاختبار معايير ومزايا وعيوب يجب مراعاتها.  يهدف هذا البحث إلى الكشف عن توزيع وتنويع بنود اختبار النحو للصف الثالث بالمدرسة المتوسطة بمدينة باتو. يعتبر البحث بحثا نوعيًا ووصفيًا حيث أنه يصف عينة البحث وفق نظرية ويكشف الظواهر الخفية. عينة البحث الأولية هي بنود اختبار النحو للصف الثالث المتوسط للعام الدراسي 2019-2020 ومحتوياتها مأخوذة من الكتاب المقرر "النحو الواضح". وخلصت الدراسة أنه قد قام المدرس بتنويع الاختبارات التي تنقسم إلى أربعة أنواع من الاختبارات التي تشمل الاختبار الموضوعي وغير الموضوعي مثل الاختيار من متعدد والإجابة القصيرة والتكملة والمقال. والإعداد الشامل من إداريات التقويم، مثل مخطط بنود الاختبار لأنه يساعد معدّ الاختبار على تطوير مهارات إعداد بنود الاختبار. الكلمات الرئيسية: نحو ، تنويع ، تقويم ، بنود الاختبار